Implementasi strategi pembelajaran Adaptif untuk anak tunarungu dalam konteks sekolah inklusi di kota Medan - Isah Dwi Putri Siregar; Boris Tubbur Manurung, Alief Bintang Zulhazzi; Kenshiro saragih, Dirga Leonardo Samosir; Johannes Situmorang, Frengkiwan Putra Sinaga; Yan Indra Siregar, Ahmad Basyaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to analyze the implementation and effectiveness of adaptive learning strategies for deaf children (ABK Tunarungu) in inclusive school environments. Inclusive education emphasizes the right of every child to learn together, but often the challenge of adapting curriculum and communication methods is a major obstacle for deaf students. This qualitative case study research was conducted at the Education Office of SLB NEGERI AUTIS, Medan City, with regular class teachers, special guidance teachers (GPK), and deaf students as subjects. The results indicate that the most effective adaptive strategy is a combination of Total Communication, the extensive use of visual-kinesthetic media, and a structured Individual Learning Program (PPI). The discussion concludes the need to improve teacher competency in Sign Language and provide adequate assistive technology to maximize the academic and social potential of deaf ABK in inclusive schools.